A proposed telepsychology program based on acceptance and commitment to develop post-traumatic growth among sons and daughters of duty martyrs at the secondary level in the Kingdom of Saudi Arabia - Alsofyani, Hanan Hamed; Alyemni, Noora Saad (Journal of Educational and Psychological Sciences, 2025)
This study aims to enhance the level of psychological health and quality of life among sons and daughters of duty martyrs, who are enrolled in the secondary stage of education. ; To this aim, the study has proposed a telepsychology program based on acceptance and commitment so as to reinforce the five dimensions of post-traumatic growth (i.e., relations with others, new potentials, personal strength, spiritual and existential change, appreciation of life) among sons and daughters of duty martyrs enrolled in the secondary stage of education thru employment of the six processes of orientation with acceptance and commitment (i.e., Acceptance, Communication with the Present, Cognitive Separation, Contextual Self, Values and Commitment), which, in turn, would act to maximize the psychological resilience and strong personal characteristics among them. The proposed orientation program is composed of 12 orientation sessions using the individual and collective orientation technique, to be virtually held through an online platform. Both researchers have made recommendations to put into force the telepsychology services into student orientation processes at all education levels. Furthermore, the proposed program was recommended to be applied to sons and daughters of duty martyrs, who are enrolled in the secondary stage of education.